Composição da avifauna, frugivoria e dispersão de sementes por aves em áreas de floresta estacional semidecidual e cerrado, no Parque Estadual de Porto ferreira, São Paulo - Athiê, Samira (2014)
In the São Paulo State predominated two large phytoecological formations: the semideciduous forests and the savanna. The extensive use of these areas mainly for cane sugar plantations and other monocultures, caused a high loss of habitats. While still play an important role in maintaining the biodiversity of the State, there is a lack of information on bird communities in this region. In this sense, we have developed a comprehensive study on the avifauna of Porto Ferreira State Park (PFSP), which protects one of the few stretches of ecological tension between semideciduous forest and savanna in São Paulo. In Chapter I, we analyze the composition and structure of PFSP‟s bird community. We recorded 207 bird species in the area, between February 2011 and October 2013, including 15 threatened/near threatened species, 22 endemic to the Atlantic Forest and two endemic to savanna. We found that the PFSP has a bird richness similar to large fragments of the region, although the most sensitive species and more demanding in the resources exploitation are less abundant compared to generalist species and to the most conserved fragments of the surroundings. In Chap. II, we evaluated the interaction between frugivorous birds and PFSP‟s ornithochoric plants. There was availability of attractive fruit throughout the year, with peak productivity between September and October, in line with the pre-reproductive period of birds and the arrival of migratory species. Despite the prevalence of generalist birds that disperse mainly small seeds of plants from the early succession stages, we found the PFSP has a diversified frugivorous bird-plant interaction network compared to other forest fragments of the State, due to the variety of available environments, connection with other surroundings fragments and its medium size and rounded shape, softening the matrix impact. In Chap. III, we evaluated the potential of bird perches in increasing the seed rain in an abandoned pasture within the PFSP limits. Therefore, we installed seed traps under natural perches (living trees) and artificial, noting the number of deposited seeds increased proportionally to the amount of landing perches structures. Natural perches also provided other resources for birds, such as fruits, insects and shelter, making them more attractive. We conclude that natural perches and artificial perches with more elaborate architecture showed greater efficiency in attracting seed-disperser birds and increasing the seed deposition, being the most recommended for this area recovery and for ecological restoration projects.